Evaluating the Use of Tactile Shapes in Associative Learning for People Who Are Blind. (July 2022) - Gupta, Richa; Mannheimer, Steve; Madhusudan Rao, P. V.; Balakrishnan, Meenakshi
Introduction: This work investigates if simple two-dimensional (2D) tactile shapes can facilitate encoding, retention, and retrieval of associated information in the form of one-word labels. It also questions the need for the resemblance of tactile graphics with respective visual referents.Methods: Four experiments were conducted using recall tasks with verbal and tactual triggers. Students who are blind from schools for blind students in Indianapolis, Indiana (USA) and New Delhi (India) participated in these experiments. Participants learned 12 shapes with assigned (two sets of) one-word labels categorized as consonant, dissonant, or abstract. Recall tasks were conducted after 1 week and after 4 months using verbal and tactual triggers.Results: The results of experiment 1 show that recall performance for consonant associations was higher than that for dissonant and abstract. Experiment 2 shows the recall performance using orally narrated verbal triggers, while experiments 3 and 4 use tactile triggers (both verbal and shape). Additionally, in experiment 4, the participants were observed recalling most associations after 4 months. Tactile verbal triggers (braille) invoked better recall accuracy as compared to tactile shape triggers.Discussion: The results and discussion with schema theory suggest that resemblance to visual referent (or similarity of tactile shape with real-life visual stimuli) is not necessary for learning associated labels. Additionally, simple 2D tactile shapes can support long-term retention of associated verbal information. The presence of primacy effect (better retention of first few associations) and distinctiveness effect (better retention of unique associations).Implications for Practitioners: The inferences of this work can influence the redesign of educational material and pedagogy for students with blindness by: (1) contributing to the development of a standardized set of symbols with associated meanings and using them for book annotation or indicating the genre of a graphic; (2) using simple tactile images instead of complex "visually correct" images.